Response of Temperate, Subtropical and Tropical Soybean Genotypes to Type-B Overflow Tidal Swamp of Indonesia - Danner Sagala; Munif Ghulamahdi; Trikoesoemaningtyas Trikoesoemaningtyas; Iskandar Lubis; Tatsuhiko Shiraiwa; Koki Homma (AGRIVITA, Journal of Agricultural Science, 2018)
Twenty-nine soybean genotypes originating from various countries were evaluated on the tidal swamp of Indonesia to obtain information of agronomic character diversity as the soybean response to the environment and to obtain adaptive genotypes that can be used to develop soybean genotypes for the land. This study was conducted in a complete randomized block design with 3 replications. Diverse genetic backgrounds, countries and climatic regions of the 29 soybean genotypes were responsible for the difference in agronomic responses among the genotypes. All temperate and sub-tropical genotypes were able to produce seeds in the tropical type-B overflow tidal swamp. Adaptability based on seed yield resulted in 1 highly adaptive, 17 adaptive, 5 moderately adaptive and 6 non-adaptive genotypes. Adaptive and highly adaptive genotypes produced 1.56 - 2.58 tons ha-1 of seeds. Karasumame (Naihou), a subtropical genotype, produced the highest seed yield which was 65% higher than Indonesia average soybean productivity and 225% higher than soybean productivity with non-saturated soil culture technology on the tidal swamp. This study concluded that temperate and subtropical genotypes could be used as germplasm sources for soybean development in the tropical type-B overflow tidal swamp in Indonesia.